The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10648-020-09536-y
|View full text |Cite|
|
Sign up to set email alerts
|

Student Teachers’ and Experienced Teachers’ Professional Vision of Students’ Understanding of the Rational Number Concept

Abstract: The aim of this study was to investigate differences in student teachers’ and experienced teachers’ professional vision in natural settings and to elicit clues of the relation of in-the-moment noticing and instruction quality of students’ understanding of rational number concept. Rational number concept challenges both students and teachers because of natural number bias that learning of rational numbers is vulnerable to. Accurate professional vision and adequate instructions are needed to enhance students’ un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
1
23
0
2
Order By: Relevance
“…Indeed, there are correlational data supporting this contention (see Weber et al 2018, Kersting et al 2012). On the other hand, especially the study by Pouta et al (2020) showed that the experienced teachers in their study reflected about the videos of their teaching in a less sophisticated manner than the student teachers did. But nevertheless, the experienced teachers were far more successful in scaffolding students' mathematical thinking than the student teachers.…”
Section: Critical Remarks On a Promising Research Paradigm And Avenues For Future Researchmentioning
confidence: 94%
See 2 more Smart Citations
“…Indeed, there are correlational data supporting this contention (see Weber et al 2018, Kersting et al 2012). On the other hand, especially the study by Pouta et al (2020) showed that the experienced teachers in their study reflected about the videos of their teaching in a less sophisticated manner than the student teachers did. But nevertheless, the experienced teachers were far more successful in scaffolding students' mathematical thinking than the student teachers.…”
Section: Critical Remarks On a Promising Research Paradigm And Avenues For Future Researchmentioning
confidence: 94%
“…Thus, successful implementation of withitness implies that a teacher has successfully established the mutual belief (see Clark 1996) that s/he is willing and able to detect and to prohibit every single disruptive behavior that occurs in the classroom. Such a transactional or communicational perspective on teaching is indeed adopted by several papers in this special issue (see Haataja et al 2020;Pouta et al 2020;Wyss et al, 2020). Hence, in learning to implement withitness effectively in the classroom, the demand on teacher students is mainly communicational rather than observational.…”
Section: Critical Remarks On a Promising Research Paradigm And Avenues For Future Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…Most studies that we analyzed used either a questionnaire (e.g., Observer; Blomberg et al, 2013), an interview (Es and Sherin, 2006), or a written commentary (Vondrova and Zalska, 2012). Only four of the studies used eye-tracking, and only two of those in the act of teaching (Pouta et al, 2020;Seidel et al, 2020).…”
Section: Professional Vision Outside the Act Of Teachingmentioning
confidence: 99%
“…Observation studies (direct observation, video studies) offer an outsiders' perspective, stimulated recalls provide insights removed from the immediacy of the classroom. Recently, eye-tracking has been introduced as a method to study teacher's perspective in the moment of teaching (Cortina et al, 2015;Dessus et al, 2016;McIntyre et al, 2017;Stürmer et al, 2017;Pouta et al, 2020;Smidekova et al, 2020). The rationale behind using eye-tracking studies is the eye-mind hypothesis, or what is attended to by the eye is processed by the mind (Duchowski, 2007, s. 3).…”
Section: Introductionmentioning
confidence: 99%